High-performance of anti-bacterial composite membrane prepared from polyethersulfone-polyethylene glycol-silver nanoparticles - Afrillia Fahrina; Nasrul Arahman; Muhammad Roil Bilad; Sri Aprilia; Sri Mulyati; Bahar Yavuztürk Gül; Ayse Yuksekdag; Sevde Korkut; Ismail Koyuncu; Muhammad Aziz; Mathias Ulbricht (South African Journal of Chemical Engineering, 2024)
A bench-scale study of river water treatment using composite polyethersulfone (PES) membrane was carried out. Polyethylene glycol-silver nanoparticles (PEG-AgNPs) additive was designed to support the simultaneous filtration and disinfection performance of PES membranes via in situ incorporation. Significant improvements in the PES membranes after modification with PEG-AgNPs were observed. The experimental results showed that the PEG-AgNPs increased the PES membrane water flux from 2.87 to 172.84 L/m2·h. The anti-fouling test of the PES membrane toward humic acid molecules after the addition of PES/PEG-AgNPs increased the reversible fouling and decreased the irreversible fouling. In terms of filtration performance, the PES/PEG-AgNP membranes showed high filtration performance, with a water disinfection ability of 99.99 %. Moreover, the leach of silver particles from the PES membrane forced by ultrasonication was <50 ppb, indicating the security and stability of the PES/PEG-AgNP membrane.